Unilateral pulmonary edema during laparoscopic resection of adrenal tumor - Smita Prakash; Pavan Nayar; Pooja Virmani; Shipra Bansal; Mridula Pawar (Wolters Kluwer Medknow Publications, 2015)
Despite technological, therapeutic and diagnostic advancements, surgical intervention in pheochromocytoma may result in a life-threatening situation. We report a patient who developed unilateral pulmonary edema during laparoscopic resection of adrenal tumor.